Clinical-psychopathological analysis of depressive disorders of oncological patients - Isaenko, S. V. (Journal of Education, Health and Sport, 2016)
Cancer has a strong impact on a human’s psyche and causes a number of negative emotions among which deep depression, suicidal thoughts and attempts are the most dangerous. Mental pathology has a significant adverse effect on the clinical and social outcomes of oncological diseases, reduces survival rates, level of adaptation and quality of life, as well as attachment to pathogenetic treatment. The objective: to investigate clinical and psychopathological peculiarities of the formation and the course of depressive disorders and suicidal behavior in cancer patients. 78 women and 76 men aged 25-55 years old with oncology had been examined. They had pathology of stages I and II without brain localization in which disorders of adaptation, in the form of depressive reaction (F43.21, F43.22) (48.4%); moderate and severe depressive episode (F32.1, F32.2) (38.2%), organic depressive disorder (F06.32) (13.4%) were diagnosed. A program of differentiated prophylaxis of suicidal behavior in cancer patients with depressive disorders was developed and tested.